Macropinocytosis-Like HIV-1 Internalization in Macrophages Is CCR5 Dependent and Leads to Efficient but Delayed Degradation in Endosomal Compartments - Gobeil, Lise-Andrée (American Society for Microbiology, 2013)
HIV-1 endocytosis by a macropinocytosis-like mechanism has been shown to lead to productive infection in macrophages. However, little is known of this pathway. In this study, we examined HIV-1 endocytosis using biochemical approaches and imaging techniques in order to better understand the mechanisms that allow for productive infection of these cells via the endosomal pathway. We show here that this macropinocytosis-like mechanism is not the sole pathway involved in HIV-1 endocytosis in macrophages. However, this pathway specifically requires CCR5 engagement at the cell surface, which in turn suggests that the virus and its coreceptor are present in the endosomal environment simultaneously. Furthermore, although we observed efficient viral degradation following endocytosis, analyses of HIV-1 transport through the endolysosomal pathway revealed that viral degradation is delayed following endosomal internalization, possibly allowing the virus to complete its fusion.